Espaços da cor nas fases de um processo - Moutinho, Natacha Antão, 1975- (2018)
The focus of this research is the study of the phenomenon of colour and its role in the sketches made during the design processes. We wish to understand the space of colour in the context of architectural design, how it is applied, used and explored, and what consequences or effects it may have on the development of the design project and the draftsman. The first step taken in this investigation was to collect and read the bibliographic material on colour and drawing, supported by specialist’s consults within this area of study. In addition, it was necessary to observe architect’s sketches that were object of study and comparison, being necessary to determine and constitute parameters of observation. This study aims to contribute to a better understanding of the use of colour in the practice of drawing, in the design process of analysis, conception and illustration, as a medium for design thinking